Less complicated adaptive equalization for UWB channels - WANG Yi-ming1; 2 ZHU Hong-bo1 (Tongxin xuebao)
A new adaptive equalization technology aiming at the intersymbol and interuser interferences in the multiuser UWB channels was presented specially for DS-UWB/TH-UWB receivers.Its computational complexity and convergence rate were compared with the traditional algorithms.The research results show that the computational complexity of this technology is less than employing RLS method solely and the convergence rate of this technology is farther off employing LMS method solely.